Manajemen Pengembangan Pendidikan Karakter Berbasis Religi (Studi Multi Situs di SMPN 24 dan SMPN 27 Banjarmasin): Management of Religious-Based Character Education Development (Multi-Site Study at SMPN 24 and SMPN 27 Banjarmasin) - Rilo Pambudi Triantoro; Aslamiah Aslamiah; Novitawati Novitawati (ITScience (Information Technology and Science), 2026)
This study aims to describe and analyze the management of religious-based character education development through principal leadership, teacher empowerment, and the use of the environment as a learning resource at SMP Negeri 24 Banjarmasin and SMP Negeri 27 Banjarmasin. This study is motivated by the phenomenon of moral degradation among students in the digital era, which demands strengthening religious values as a foundation for character formation. This study uses a qualitative, multi-site design. Data collection techniques included in-depth interviews, observations, and document analysis. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, as well as cross-site analysis to identify similarities and differences in managerial practices across both schools. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that: 1. principal leadership plays a strategic role in formulating policies, building a religious culture, and integrating religious values into school programs; 2. teacher empowerment is carried out through active involvement in program planning and implementation, exemplary attitudes, and integration of religious values ??into daily learning and habits; and 3. the use of the school and social environment as learning resources to strengthen the internalization of religious values through habituation activities, social interactions, and direct experiences of students. Cross-site analysis shows variations in managerial approaches, but both share a commitment to building religious character through the synergy of leadership, teachers, and school culture. This study confirms that planned, systematic, and sustainable management of the development of religious-based character education can strengthen students’ moral knowing, moral feeling, and moral action.